The double burden of malnutrition in Asia : causes, consequences, and solutions - Gillespie, Stuart (Stuart R.); Haddad, Lawrence James (New Delhi ; Thousand Oaks : Sage Publications, 2003)
"This book is the first comprehensive assessment of nutrition in Asia, a region that has the largest concentration of global malnutrition. It reviews a wide array of nutrition-relevant trends, policies, programmes, challenges and opportunities in Asia." "This book describes the main driving forces behind the groundswell of under nutrition. It sheds light on the emerging "double burden" of co-existing underweight and overweight and the linkages between these two different forms of malnutrition."--BOOK JACKET.
Machine derived contents note: List of Tables -- List of Figures and Boxes -- Preface and Acknowledgements -- -- 1 Malnutrition in Asia -- 2 Direct Nutrition Action -- 3 Developing Capacity for Nutrition Action -- 4 Indirect Nutrition-Relevant Actions -- 5 Contextual Dynamics -- 6 Financing Nutrition Interventions -- 7 The Way Forward -- -- Indexes -- References -- -- About the Authors.
Includes bibliographical references (p. [210]-225) and index.
Keywords: Malnutrition -- Asia